Некоторые особенности состояния миокарда предсердий при экспериментальном стенозе аорты - В. С. Юрасов; Э. С. Башкиров; В. В. Молчанов (Հայկական ՍՍՀ գիտությունների ակադեմիա)
Վերել աորտայի քառակի նեղացման ճանապարհով 62 ճագարների մոտ ստեղծվել է սրտի կոմպենսատոր գերլարում։ Նախասրտի և փորոքների ձևաբանական փոփոխությունները համեմատվել են QRS կոմպլեքսի և P ատամիկի վոլտաժի տեղաշարժերի հետ։ Compensatory hyperfunction of the heart (CHH( was produced in 62 rabbits by stenosing the ascending aorate to 1/4 of its original size.Morphological changes in the ventricles and atria were compared with the voltage dynamics of QRS complex and R-wave.
Keywords: Diseases of the blood and blood-forming organs; Medicine; Cardiology; Internal medicine